(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2021)
The present study aimed to evaluate carbon in a native wooded system of the Palenque Canton, Los Ríos Province, Ecuador; where two quadrants were established at random, 50 x 50m2 inside the native forest of the Pedro Franco Dávila Scientific Station, dasometric measurements were made that were taken in the study field as diameter at chest height (DBH), height total (H) and commercial volume (Vc), where the direct or destructive method was used to have the trunk, stem, branch, roots, leaves and leaf litter samples that were sent to the laboratory to obtain carbon (c) by the method of elemental analysis. Registering in quadrant A1 125 individuals, 12 species, 12 genus and 9 family quadrant A2 135 individuals, 12 species, 12 genus and 8 family; In both quadrants, the most representative family was Morácea, and the Tillo prieto species (Sorocea sarcocarpa) had a greater presence in both quadrants; biomass with a total for the studied area of 30.17 T (c), branch volume 3.65 m3, commercial volume of an individual is 4.8m3 root volume 1.63 m3, leaves 266.6 T (c), litter 634, 6 T (c), giving a total in the sample area with 46 individuals of Tillo prieto (Sorocea sarcocarpa) of 31.09 T (c). In conclusion, Tillo prieto (Sorocea sarcocarpa), constitutes a population of young trees by having 11 individuals in the height class between 7-13.99 in quadrant A1, with seven individuals in the height class between 6-8.99 in the quadrant A2.